The dynamics of migration and their impact on the country of origin: A case study of Senegalese labour migrants on the Cape Verdean Island Boa Vista and their relatives at home - Jung, Philipp (2013)
As a result of economic growth and the extension of the tourism sector since the beginning of the new millennium, Cape Verde has become a destination for a growing number of migrants from continental West Africa, especially from other ECOWAS member states. After migrants from Guinea-Bissau, Senegalese build the second biggest community of ECOWAS migrants. This thesis addresses migration processes between Senegal and the Cape Verdean Island Boa Vista. The focus lies on migration motives, migration patterns and aspects, which influence the choice of Cape Verde as destination. Furthermore it analyses the flow of remittances and how the situation of the migrants on the island Boa Vista influences this monetary flow. Finally, the influence of these remittances on the lives of the migrants’ families in Senegal and how they are used is examined. Households in Senegal spend a high percentage of their income on food, and they often depend on the support of migrated household members. Families try to minimize risk of food insecurity through the diversification of income resources, and migration is one coping strategy to do so. Empirical data from research in Cape Verde and Senegal are used for the analysis of the above mentioned factors. This thesis seeks to add knowledge about remittances in the environment of intra-continental migration in West Africa, and more specifically about the relatively new and until now barely researched phenomenon of immigration to Cape Verde.